2017
DOI: 10.1039/c7ta04608a
|View full text |Cite
|
Sign up to set email alerts
|

A formamidinium–methylammonium lead iodide perovskite single crystal exhibiting exceptional optoelectronic properties and long-term stability

Abstract: Mixed cation formamidinium–methylammonium perovskite alloy single crystal outstrips the sole cation single crystal in both long-term stability and optoelectronic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(127 citation statements)
references
References 49 publications
3
121
0
Order By: Relevance
“…Single‐crystalline and thin‐film samples of our mixed‐cation tin perovskite appear black and have great stability in air. Kubicki et al found that black hybrid FA + /GA + lead triiodide perovskite crystals were thermodynamically unstable and became yellow in a few hours; moreover, crystal reorientation was observed in their mother structure (FAPbI 3 ) . Phase transition occurred at room temperature has been reported for FAPbI 3 but not for FASnI 3 because it happened at much lower temperatures (125–150 K) for which the black phase of FASnI 3 is stable at room temperature .…”
Section: Photovoltaic Parameters Of the Perovskite Solar Cells Fabricmentioning
confidence: 99%
“…Single‐crystalline and thin‐film samples of our mixed‐cation tin perovskite appear black and have great stability in air. Kubicki et al found that black hybrid FA + /GA + lead triiodide perovskite crystals were thermodynamically unstable and became yellow in a few hours; moreover, crystal reorientation was observed in their mother structure (FAPbI 3 ) . Phase transition occurred at room temperature has been reported for FAPbI 3 but not for FASnI 3 because it happened at much lower temperatures (125–150 K) for which the black phase of FASnI 3 is stable at room temperature .…”
Section: Photovoltaic Parameters Of the Perovskite Solar Cells Fabricmentioning
confidence: 99%
“…It was recently reported that FAPbI3 single crystal and wafer are able to withstand higher temperatures compared to polycrystalline thin films counterparts. 37,89 Although these single-crystals show good photoelectric properties, they have 19 | P a g e poorer thermal stability compared to completely inorganic perovskites 82 due to the presence of volatile organic moieties. Therefore, highly thermostable optoelectronic properties are exhibited by the allinorganic SCPs.…”
Section: Temperaturementioning
confidence: 99%
“…Perovskite films are commonly used in metal-halide solar cells with increasingly high PCE, however, the exact mechanism and the detailed structures of the perovskite film are still ambiguous. Consequently, much research has been performed on the stability [5][6][7][8], PCE [9,10], and toxicity [11,12] of the photosensitive film of the perovskite solar cell. In general, the perovskite solar cell is composed of the electrodes, electron transport layer, metal-halide perovskite film, and the hole transport layer.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the perovskite solar cell is composed of the electrodes, electron transport layer, metal-halide perovskite film, and the hole transport layer. To reduce the influence of heterojunctions in solar cells, perovskite structures with single-crystal quality are a good candidate to detect related physic properties, such as giant photostriction [13], long range of electron-hole diffusion [14], structural and optoelectronic characteristics [15], harvesting of below-bandgap light absorption [16], optoelectronic properties [5], and ferroelectric and piezoelectric properties [17]. Moreover, perovskite crystals can also be utilized to detect related novel physical phenomenon, such as the quantification of re-absorption and re-emission processes, to determine photon recycling efficiency [18] and the detection of photons [19,20].…”
Section: Introductionmentioning
confidence: 99%